ANALISIS INDIKATOR MOTIVATIONAL DETERIORATION PERWIRA LAUT PT PELNI (PERSERO) JAKARTA DALAM PENEMPATAN TIPE KAPAL - Reno Fandika (JCI Publisher, 2025)
The purpose of this study is to determine and analyze the indicators of motivational deterioration in marine officers of PT PELNI (Persero) Jakarta related to their preferences in ship type placement (2000 pax, 1000 pax, and 500 pax), identify the main indicators that cause the decline in motivation of marine officers of PT PELNI (Persero) Jakarta, and analyze the relationship between indicators of motivational deterioration with marine officers' preferences for different types of ships. In this study, researchers used a qualitative method with a descriptive form and emphasized the use of motivation theory and the concept of motivational deterioration to analyze indicators of motivational deterioration of marine officers of PT PELNI (Persero) Jakarta in ship type placement. From the results of the study it is known that there is a salary gap that has not been adjusted to the applicable career pattern for the promotion path, which is one of the main factors triggering the decline in motivation of marine officers of PT PELNI (Persero) Jakarta in ship type placement, as well as other factors that contribute to motivational deterioration, namely the absence of a clear career pattern system and a promotion path that is not running optimally, this condition affects the preferences and performance of marine officers in assignments on various types of ships. The data was obtained from books, scientific journals, official company and government websites, company directors' decrees, and valid online media articles.